Haplotype variation in the ACE gene in global populations, with special reference to India, and an alternative model of evolution of haplotypes - Farheen, Shabana (Springer Netherlands, 2011)
Angiotensin-I-converting enzyme (ACE) is known to be associated with human cardiovascular and psychiatric pathophysiology. We have undertaken a global survey of the haplotypes in ACE gene to study diversity and to draw inferences on the nature of selective forces that may be operating on this gene. We have investigated the haplotype profiles reconstructed using polymorphisms in the regulatory (rs4277405, rs4459609, rs1800764, rs4292, rs4291), exonic (rs4309, rs4331, rs4343), and intronic (rs4340; Alu [I/D]) regions covering 17.8 kb of the ACE gene. We genotyped these polymorphisms in a large number of individuals drawn from 15 Indian ethnic groups and estimated haplotype frequencies. We compared the Indian data with available data from other global populations. Globally, five major haplotypes were observed. High-frequency haplotypes comprising mismatching alleles at the loci considered were seen in all populations. The three most frequent haplotypes among Africans were distinct from the major haplotypes of other world populations. We have studied the evolution of the two major haplotypes (TATATTGIA and CCCTCCADG), one of which contains an Alu insertion (I) and the other a deletion (D), seen most frequently among Caucasians (68%), non-African HapMap populations (65–88%), and Indian populations (70–95%) in detail. The two major haplotypes among Caucasians are reported to represent two distinct clades A and B. Earlier studies have postulated that a third clade C (represented by the haplotypes TACATCADG and TACATCADA) arose from an ancestral recombination event between A and B. We find that a more parsimonious explanation is that clades A and B have arisen by recombination between haplotypes belonging to clade C and a high-frequency African haplotype CCCTTCGIA. The haplotypes, which according to our hypothesis are the putative non-recombinants (PuNR), are uncommon in all non-African populations (frequency range 0–12%). Conversely, the frequencies of the putative recombinant haplotypes (PuR) are very low in the Africans populations (2–8%), indicating that the recombination event is likely to be ancient and arose before, perhaps shortly prior to, the global dispersal of modern humans. The global frequency spectrum of the PuR and the PuNR is difficult to explain only by drift. It appears likely that the ACE gene has been undergoing a combination of different selective pressures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11568-011-9153-6) contains supplementary material, which is available to authorized users.